How anthropogenic noise affects foraging. (4th July 2015) - Luo, Jinhong; Siemers, Björn M.; Koselj, Klemen
Abstract The influence of human activity on the biosphere is increasing. While direct damage (e.g. habitat destruction) is relatively well understood, many activities affect wildlife in less apparent ways. Here, we investigate how anthropogenic noise impairs foraging, which has direct consequences for animal survival and reproductive success. Noise can disturb foraging via several mechanisms that may operate simultaneously, and thus, their effects could not be disentangled hitherto. We developed a diagnostic framework that can be applied to identify the potential mechanisms of disturbance in any species capable of detecting the noise. We tested this framework using Daubenton's bats, which find prey by echolocation. We found that traffic noise reduced foraging efficiency in most bats. Unexpectedly, this effect was present even if the playback noise did not overlap in frequency with the prey echoes. Neither overlapping noise nor nonoverlapping noise influenced the search effort required for a successful prey capture. Hence, noise did not mask prey echoes or reduce the attention of bats. Instead, noise acted as an aversive stimulus that caused avoidance response, thereby reducing foraging efficiency. We conclude that conservation policies may seriously underestimate numbers of species affected and the multilevel effects on animal fitness, if the mechanisms of disturbance are not considered.